2011
DOI: 10.1002/ccd.22817
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric catheterization laboratory anticoagulation with bivalirudin

Abstract: PK/PD response of bivalirudin in the pediatric population is predictable and behaves in a manner similar to that in adults. Using adult dosing, bivalirudin safely provided the expected anticoagulant effect in the pediatric population undergoing intravascular procedures for congenital heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 16 publications
3
36
0
1
Order By: Relevance
“…[10][11][12] Disadvantages include the lack of an available antidote, although it can be removed by dialysis or ultrafiltration after CPB, 14 and limited pediatric experience. 8,[13][14][15][16][17] The initial bivalirudin dose in our patients was based on estimates of the glomerular filtration rate as measured by the Schwartz formula and following suggestions by Warkentin et al 10 All patients had normal renal function, with the exception of Patient 2. Once therapeutic levels were achieved as determined by PTT, few dosage adjustments were required.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Disadvantages include the lack of an available antidote, although it can be removed by dialysis or ultrafiltration after CPB, 14 and limited pediatric experience. 8,[13][14][15][16][17] The initial bivalirudin dose in our patients was based on estimates of the glomerular filtration rate as measured by the Schwartz formula and following suggestions by Warkentin et al 10 All patients had normal renal function, with the exception of Patient 2. Once therapeutic levels were achieved as determined by PTT, few dosage adjustments were required.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to argatroban, bivalirudin is a selective, reversible direct thrombin inhibitor. Recent pediatric investigations have begun to define the dose and safety profile of bivalirudin for neonatal VTE [46] as well as its efficacy in pediatric interventional cardiology [47]. An additional Phase I study investigating the safety and efficacy of bivalirudin in children up to age 18 has recently completed accrual [48].…”
Section: New Anticoagulant Agentsmentioning
confidence: 99%
“…As outlined before, bivalirudin dose response in non-neonate pediatric patients (the group of interest in the present study) has been shown to be comparable to adults. 6 Of note, the target ACT value 4480 seconds for the ACT Plus device (eg, standard kaolin-activated assay) used in Dr. Hasija's study was rather high, when compared to previous investigations in adults and other reported pediatric cases. 5,9 In most articles, values of approximately 300 to 400 seconds showed a good correlation with the targeted bivalirudin concentrations of 10 to 15 mg/mL during CPB.…”
mentioning
confidence: 61%
“…the fact that the pharmacokinetic profile of bivalirudin, using the established dosing protocols for percutaneous intervention in adults, only has been assessed in small groups of pediatric patients with congenital heart disease undergoing percutaneous intravascular procedures. 6 These data suggest that the pharmacokinetics of bivalirudin in small infants and older children is predictable and comparable to adults, while neonates present a different dose-response profile.…”
mentioning
confidence: 79%